2023
DOI: 10.55217/102.v16i1.606
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of logistics management on organizational performance: New evidence from the manufacturing industry

Abstract: The goal of this study is to determine how logistics management affects the organizational performance of ten Ghanaian roofing sheet manufacturing companies. To analyze the influence of logistics management on organizational outcome, the researchers employed multiple linear regression. The findings showed that the aspects of logistics management that have a beneficial impact on organizational performance include inventory management, physical distribution, and warehouse management. Logistics plays an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The physical movement of finished products is pivotal as unless products do not reach the target customers, the demand or customer satisfaction cannot be fulfilled (Kalkan, 2018). According to Adelwini et al (2023) transportation ensures delivery of products from the point of origin to the point of consumption. Pakurar et al (2020) declared that timely availability of products is of prime importance as only then can the reason for manufacturing a product be attained.…”
Section: Transportationmentioning
confidence: 99%
See 2 more Smart Citations
“…The physical movement of finished products is pivotal as unless products do not reach the target customers, the demand or customer satisfaction cannot be fulfilled (Kalkan, 2018). According to Adelwini et al (2023) transportation ensures delivery of products from the point of origin to the point of consumption. Pakurar et al (2020) declared that timely availability of products is of prime importance as only then can the reason for manufacturing a product be attained.…”
Section: Transportationmentioning
confidence: 99%
“…As a result of the findings, it is suggested that industrial companies concentrate on all aspects of logistics operations such as purchasing, storage, transportation, distribution, handling, packaging, customer service and scheduling in the industrial sector. Adelwini et al (2023) investigated the effects of logistics management on organizational performance employing multiple linear regression. The findings showed that the aspects of logistics management that have a beneficial impact on organizational performance include inventory management, physical distribution and warehouse management.…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation